2016
DOI: 10.1007/s40865-016-0045-2
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Arrests Among Indigenous Adolescents: a Longitudinal Analysis of Community, Family, and Individual Risk Factors

Abstract: Purpose North American indigenous (American Indian/Canadian First Nations) adolescents are overrepresented in the juvenile justice systems in the USA and Canada. One explanation advanced for disproportionate numbers of racial and ethnic minorities in the justice systems is the unequal distribution of risk factors across groups. The purpose of this study is to investigate the prevalence of and risk factors for first arrest within a population sample of indigenous adolescents. Methods The data come from an 8-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…What the current study elucidated most clearly, though, was the paucity of research related to Indigenous peoples and the criminal justice system. This dearth, noted within both published and unpublished research literatures, can probably be explained in large part by the lack of high quality and detailed data being recorded by provincial corrections, police agencies, and youth and adult courts (Department of Justice, 2018;Reitmanova & Henderson, 2016;Reasons et al, 2016;Reid, 2017;Rudin, 2005;Sittner & Gentzler, 2016;Walter & Andersen, 2016;Zimmerman, 1992). According to Reid (2017), increasingly there are delays in the publications of court statistics by Statistics Canada.…”
Section: Discussionmentioning
confidence: 99%
“…What the current study elucidated most clearly, though, was the paucity of research related to Indigenous peoples and the criminal justice system. This dearth, noted within both published and unpublished research literatures, can probably be explained in large part by the lack of high quality and detailed data being recorded by provincial corrections, police agencies, and youth and adult courts (Department of Justice, 2018;Reitmanova & Henderson, 2016;Reasons et al, 2016;Reid, 2017;Rudin, 2005;Sittner & Gentzler, 2016;Walter & Andersen, 2016;Zimmerman, 1992). According to Reid (2017), increasingly there are delays in the publications of court statistics by Statistics Canada.…”
Section: Discussionmentioning
confidence: 99%
“…Social factors, such as associating with delinquent peers (e.g., Monahan et al, 2014; Sittner & Gentzler, 2016) and gang involvement (e.g., Tapia, 2011), also are correlated with juvenile arrest. For instance, Sittner and Gentzler (2016) found that youths who reported having a close friend who had been in trouble with the police were more than twice as likely to be arrested compared to those who did not associate with delinquent peers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social factors, such as associating with delinquent peers (e.g., Monahan et al, 2014; Sittner & Gentzler, 2016) and gang involvement (e.g., Tapia, 2011), also are correlated with juvenile arrest. For instance, Sittner and Gentzler (2016) found that youths who reported having a close friend who had been in trouble with the police were more than twice as likely to be arrested compared to those who did not associate with delinquent peers. Debate persists as to why this may be the case (e.g., possible self-selection into delinquent peer groups), though the literature suggests that parental monitoring may be an effective form of social control that provides some protection against arrest (Kirk, 2009; Unnever et al, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations